The Relationship Of Spiritual Support With Anxiety Levels And Spiritual Adaptation Of Pregnant Women - Muaffikah Putri; Andi Alifia Ayu Delima; Rini Fitriani; Rahadi Arie Hartoko; Takdir (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Background: Spiritual support is assistance provided to individuals or families to maintain and deepen spiritual beliefs and adaptations that have the aim of fulfilling human life needs, both biologically, psychologically, and socially. Meanwhile, anxiety is an excessive sense of worry that arises in a person. Objectives: This study aims to determine the relationship between spiritual support with pregnant women's anxiety levels and spiritual adaptation. Methods: The research method used in this study is observational with a cross-sectional approach. The sampling technique in this study was total sampling with a sample size of 42 pregnant women at the Family Clinic in Wajo Regency who met the inclusion criteria. The instrument used to collect data in this study was a questionnaire. Quantitative data analysis using the Chi-Squrare test 2x2 table. Results: The results of the relationship test using the chi-square test showed a p-value of 0.000 which is smaller than 0.05. This shows that there is a significant relationship between spiritual support and spiritual adaptation. And the relationship test results using the chi-square test show a p-value of 0.000 which is smaller than 0.05. This indicates a significant relationship between spiritual support and anxiety levels. Conclusion: There is a significant relationship between spiritual support and anxiety levels and spiritual adaptation of pregnant women at the Family Clinic in Wajo Regency in 2021.